2011
DOI: 10.1007/s12265-011-9327-6
|View full text |Cite
|
Sign up to set email alerts
|

The Management of Thrombotic Lesions in the Cardiac Catheterization Laboratory

Abstract: Plaque rupture with superimposed thrombosis is the major mechanism of acute coronary syndromes. Although angiography underestimates the presence of thrombi, their detection is a poor prognostic indicator which is proportional to their size. Although emergent percutaneous coronary intervention (PCI) in the setting of ST elevation myocardial infarction (STEMI) and early PCI in the setting of unstable angina and non-STEMI were shown to be preferred strategies, the presence of angiographic thrombosis by virtue of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 90 publications
0
4
0
1
Order By: Relevance
“…Myocardial infarction (MI) is the result of an acute occlusion of a coronary artery due to plaque rupture and subsequent thrombosis [27]. The prognosis of patients suffering from MI is mainly determined by the infarct size (IS) [14], which in turn depends on the inflammatory response of the myocardium.…”
Section: Introductionmentioning
confidence: 99%
“…Myocardial infarction (MI) is the result of an acute occlusion of a coronary artery due to plaque rupture and subsequent thrombosis [27]. The prognosis of patients suffering from MI is mainly determined by the infarct size (IS) [14], which in turn depends on the inflammatory response of the myocardium.…”
Section: Introductionmentioning
confidence: 99%
“…In the setting of ACS or when faced with a thrombotic lesion for which percutaneous coronary intervention (PCI) is being considered, adjunctive pharmacological therapy delivered intravenously or via the intracoronary route should aim at the prevention of thromboembolic events associated with PCI, and the reversal of such events if they occur. The interventional cardiologist is faced with the hard task of managing lesions with high thrombotic burden, which is more prevalent when earlier catheterization is performed [6]. The mechanical manipulation of such lesions is associated with a high incidence of periprocedural complications at least in part due to a high incidence of distal embolization [7].…”
Section: Discussionmentioning
confidence: 99%
“…In the PREPARE (Proximal Embolic Protection in Acute MI and Resolution of ST-Elevation) trial, the use of the Proxis proximal protection device was compared to conventional PCI and showed improved microvascular flow as reflected by improved ST-segment resolution in the proximal protection arm [ 35 ]. Results from smaller randomized trials and registry data using various EPDs in native vessel PCI have shown equally disappointing clinical results (Table 2 ) [ 33 , 36 - 37 ].…”
Section: Embolic Protection Devices In Native Vessel Percutaneous Intmentioning
confidence: 99%
“…Several mechanisms have been proposed for the negative results of EPDs in native coronary vessel thrombotic lesions: the bulky nature of these EPD devices may themselves cause embolization, the presence of side branches that cannot be protected, incomplete protection with the device due to either incomplete device/vessel apposition or pore size that fails to capture particles <100μm within the filter, and predilation is often necessary to facilitate delivery of the device, limiting the benefit as distal embolization occurs during the pre-dilation balloon inflation [ 13 , 37 ]. In addition, the EPD might only be beneficial in patients with large thrombus burden without multiple side branches proximal to the protection device.…”
Section: Embolic Protection Devices In Native Vessel Percutaneous Intmentioning
confidence: 99%